Ethiopia : Priorities for Ending Extreme Poverty and Promoting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2016)
This Systematic Country Diagnostic (SCD) identifies the binding constraints to reducing extreme poverty and promoting shared prosperity in Ethiopia. Achieving those goals requires a two pronged strategy of building on the strengths of past performance as well as introducing new elements. Progress in rural livelihoods drove poverty reduction in the past and will likely do so in the future. In addition, faster, and more inclusive, private sector-led structural change and ‘getting urbanization right’ are essential going forward. The report identifies two key challenges to sustainable progress: Ethiopia needs sustainably financed infrastructure that enables private investment to flourish and reduces reliance on public borrowing. It must also strengthen feedback mechanisms that inform policymakers of what works and what doesn’t so that the aspirations of a rapidly rising and better-educated working-age population can be met. The report is structured in two parts: Part A analyses the past and Part B identifies priorities for the future.